RGEC Method: Assessment Of Bank Health Levels At PT Bank Tabungan Negara (PERSERO) Tbk. Before And After Covid-19 - An Suci Azzahra; Meigia Nidya Sari (Brilliant International Journal Of Management And Tourism, 2024)
This study aims to determine the health level of PT Bank Tabungan Negara (Persero) Tbk before and after Covid-19 from the point of view of the RGEC analysis model (Risk Profile, GCG, Earning, and Capital) by analyzing the entire financial statements. The research method used in this study is to use a descriptive model of PT Bank Tabungan Negara (Persero) Tbk before (2017-2019) and during covid-19 (2020-2022). The data was then obtained by researchers using documentation techniques where the data used were financial reports to be analyzed by the Risk method (Risk-based Bank Rating) based on assessment measurements which included RGEC elements. The results of the assessment that can be concluded in the analysis of the health level of PT Bank Tabungan Negara (Persero) Tbk in terms of RGEC (Risk profile, Good Corporate Governance, Earnings, and Capital) before covid-19 in 2017-2018 in a healthy condition, while in 2019 in a fairly healthy condition and during covid-19 in 2020-2022 in a healthy condition, it is concluded that before and during covid-19 PT Bank Tabungan Negara, Tbk the bank's health level has no impact on covid-19.